Evaluation of predation pressure by wild canids on threatened wild ungulates in the Hirpora Wildlife Sanctuary, Pir Panjal Range of the Lesser Himalaya - Najar, Zakir Hussain; Quyoom, Iyaz; Ahmad, Riyaz; Alqahtani, Abdulaziz R; Bhat, Bilal A (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aims to evaluate the predation pressure of wild canids on two threatened wild ungulates, the Pir Panjal markhor (Capra falconeri cashmeriensis) and the Kashmir musk deer (Moschus cupreus) in the Hirpora Wildlife Sanctuary (HWLS). Materials and Methods: Between August 2020 and July 2022, we surveyed trails (n = 27) to collect scat samples of three canid species in the HWLS for dietary analysis. To determine the prey species, a sample of hair was taken from each fecal sample and compared with the available reference collection and published literature. We followed the total count method to estimate ungulate availability in the sanctuary. The selectivity of threatened wild ungulates by wild canids was assessed by Jacob’s selectivity index. The biomass contribution of prey items to canid species was determined by multiplying the dry weights of prey remnants by coefficients of digestibility. Results: The analysis revealed the presence of 10 different types of dietary items in red fox scats, while golden jackal and Himalayan wolf scats contained 11 identified items each, along with unidentified material. In all canid species, animal matter contributed more than plant matter. According to this study, livestock contributed the most to the biomass consumption of the three canid species. The Himalayan wolf also showed a small proportion of wild ungulates in its diet. According to Jacob’s selectivity index, the Himalayan wolf avoided wild ungulates, probably due to the extremely small population of these ungulates in the sanctuary. Conclusion: The local wild ungulate populations in the area have been reduced to a level where the wild canids cannot opt to prey on them because the costs would outweigh the benefits. Therefore, in order to restore the population of wild ungulates, other contributing factors need to be recognized and given due attention. J. Adv. Vet. Anim. Res., 12(3): 840–848, September 2025 http://doi.org/10.5455/javar.2025.l946